Análisis jurídico y comparado del Código Orgánico de la Niñez y Adolescencia, en relación a la caducidad del derecho de extinción de alimentos, se incorpore del alimentado/a estudiante, que tenga hijos. - Vivanco Jumbo, Liliana Rocio (2023)
The present work titled "Legal and Comparative Analysis of the Organic Code of Childhood and Adolescence, in relation to the expiration of the right to terminate alimony, when the student, who is a parent, has children," comprises a doctrinal, legal, and comparative study with other legislations regarding the termination of maintenance when the student, who is of legal age, has children. In the face of the requirements for the expiration of the right to alimony, decisions need to be made that should be analyzed from a social, political, and legal perspective. Socially and legally, parents are obligated to provide child support and education until their children reach the age of 21. However, when the student has children, it is done under the determination of legal capacity, and the obligated party is no longer responsible for the obligations assumed by their son or daughter. Politically, the state of need that families experience due to lack of employment must be considered, and legally, laws must be continually innovated for the benefit of society. Therefore, individuals become fully emancipated upon reaching the age of majority, and exclusive rights and obligations arise for each individual. The Organic Code of Childhood and Adolescence regulates support for children and adolescents, no longer establishing support for adults. It makes an exception for those who are studying. However, when the supported individual gets married, forms a de facto union, or has children, new obligations as a couple arise; therefore, it should be established as a cause for the expiration of alimony. Finally, this research encompasses a comprehensive analysis of legal information from a descriptive, evaluative, explanatory, and propositional perspective, under a legal framework in the field of family law. Materials and methods that supported the research were also used. Likewise, interviews and surveys were conducted with legal professionals, whose results aim to awaken a critical perspective regarding the termination of alimony when the legal-age student has children.